Proceedings of the 9th Audio Mostly: A Conference on Interaction With Sound 2014
DOI: 10.1145/2636879.2636896
|View full text |Cite
|
Sign up to set email alerts
|

Designing sound identity

Abstract: In this paper we focus through a series of interviews on the relation between sound and brand identity in the context of musical and sound design for the industry. The interviews showed that the sound design process involves stakeholders who have different domains of expertise, which leads to difficulties in the interaction between them. As a solution, we propose a methodological framework for designing sound identity supported by two communication tools: a deck of cards allowing the different stakeholders to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Warm (chaud) and round (rond) are two sound attributes that seem to share many similarities in the description of sound as observed in some works (Bernays & Traube, 2014;Carron, 2016;Zacharakis et al, 2014). Studies conducted by three of the authors of this article have observed difficulties in distinguishing the two terms in professional conversations between sound designers and industrial partners (Carron et al, 2015;Misdariis et al, 2019). Although not thoroughly documented, this issue is persistent in sound design workshops based on verbal descriptions of sound characteristics.…”
Section: A S Human Beings W E a R E U Se D Tomentioning
confidence: 72%
“…Warm (chaud) and round (rond) are two sound attributes that seem to share many similarities in the description of sound as observed in some works (Bernays & Traube, 2014;Carron, 2016;Zacharakis et al, 2014). Studies conducted by three of the authors of this article have observed difficulties in distinguishing the two terms in professional conversations between sound designers and industrial partners (Carron et al, 2015;Misdariis et al, 2019). Although not thoroughly documented, this issue is persistent in sound design workshops based on verbal descriptions of sound characteristics.…”
Section: A S Human Beings W E a R E U Se D Tomentioning
confidence: 72%
“…These are then evaluated in the testing step to select the one which fulfils requirements best. A similar three-step approach called briefing, debriefing, and validation is presented in [23]. The first step relates to the communication of the problem formulation, the second to conceptualization and sketching, and the third to evaluation.…”
Section: Sound Designmentioning
confidence: 99%
“…Verbal sketching: Sketching based on verbalizations is introduced by Carron et al [23,54] who established and validated for this purpose a sound lexicon of 35 words. The lexicon was augmented by manipulable sound examples and illustrated with pictures.…”
Section: Sketching Soundmentioning
confidence: 99%